Clinical and molecular implications of mosaicism in FMR1 full mutations - Pretto, Dalyir; Yrigollen, Carolyn M.; Tang, Hiu-Tung; Williamson, John; Espinal, Glenda; Iwahashi, Chris K.; Durbin-Johnson, Blythe; Hagerman, Randi J.; Hagerman, Paul J.; Tassone, Flora (Frontiers in Genetics, 2014)
Expansions of more than 200 CGG repeats (full mutation) in the FMR1 gene give rise to fragile X syndrome (FXS) through a process that generally involves hypermethylation of the FMR1 promoter region and gene silencing, resulting in absence of expression of the encoded protein, FMRP. However, mosaicism with alleles differing in size and extent of methylation often exist within or between tissues of individuals with FXS. In the current work, CGG-repeat lengths and methylation status were assessed for eighteen individuals with FXS, including 13 mosaics, for which peripheral blood cells (PBMCs) and primary fibroblast cells were available. Our results show that for both PBMCs and fibroblasts, FMR1 mRNA and FMRP expression are directly correlated with the percent of methylation of the FMR1 allele. In addition, Full Scale IQ (FSIQ) scores were inversely correlated with the percent methylation and positively correlated with higher FMRP expression. These latter results point toward a positive impact on cognition for full mutation, methylation mosaics with lower methylation compared to individuals with fully methylated, full mutation alleles. However, we did not observe a significant reduction in the number of seizures, nor in the severity of hyperactivity or autism spectrum disorder, among individuals with mosaic genotypes in the presentation of FXS. These observations suggest that low, but non-zero expression of FMRP may be sufficient to positively impact cognitive function in individuals with FXS, with methylation mosaicism (lowered methylation fraction) contributing to a more positive clinical outcome.